Facial Redness Increases Men's Perceived Healthiness and Attractiveness. (June 2017) - Thorstenson, Christopher A.; Pazda, Adam D.; Elliot, Andrew J.; Perrett, David I.
Past research has shown that peripheral and facial redness influences perceptions of attractiveness for men viewing women. The current research investigated whether a parallel effect is present when women rate men with varying facial redness. In four experiments, women judged the attractiveness of men's faces, which were presented with varying degrees of redness. We also examined perceived healthiness and other candidate variables as mediators of the red-attractiveness effect. The results show that facial redness positively influences ratings of men's attractiveness. Additionally, perceived healthiness was documented as a mediator of this effect, independent of other potential mediator variables. The current research emphasizes facial coloration as an important feature of social judgments.